Visualisasi Scattering Cross Section Versus Scattering Angle Pada Hamburan Rutherford Atom Timbal dengan Matrix Laboratory - Supriadi, Bambang; Nuraini, Lailatul; Istighfarini, Elma Tri; Lubna, Lubna; Mardhiana, Hana; Savana, Bunga Aurel (Jurnal Fisika Unand, 2022)
Atom is the smallest component of a chemical element that cannot be changed chemically. The concept of the atom was put forward by several scientists, one of which was Rutherford. From the results of Rutherford's experiment, it is known that most of the alpha particles fired at a thin gold plate are transmitted or scattered with a small scattering angle. In this study, the effect of incident energy (E) on the scattering cross section (Ïƒ) and scattering angle (Î˜) will be simulated using Matrix Laboratory (MATLAB). Based on the results of the research that has been done, it can be concluded that in Rutherford scattering, the greater the scattering angle, the smaller the scattering cross section. This is shown in the graph generated in the Matrix Laboratory (MATLAB) simulation in the form of a decreasing exponential graph.